A post mortem of the Green Deal: Austerity, energy efficiency, and failure in British energy policy. (November 2016) - Rosenow, Jan; Eyre, Nick
Abstract: The Green Deal was a British flagship policy intended to deliver energy efficiency retrofits at scale. About 2.5 years after its launch the programme was effectively terminated and is now seen as a dramatic policy failure. In this paper we analyse the reasons for the failure and the politics that led to the rise and the fall of the Green Deal. We conclude that even though the risks were understood and voiced by critics well in advance of the launch of the Green Deal, the logic of a subsidy free energy efficiency scheme became the accepted wisdom at the highest levels of Government, through a combination of ideology and failure to listen.